Plant Hormones - Recent Advances, New Perspectives and Applications 2022
DOI: 10.5772/intechopen.102832
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones as Plant Growth Regulators and Safe Protectors against Biotic and Abiotic Stress

Abstract: Plants are playing important role in the planet by providing food for humans and stability in the environment. Phytohormones are key regulators in various physiological processes and among the most important small signaling molecules affecting plant growth and yield production. These biochemical also initiate adaptive responses caused by external stimuli, such as biotic and abiotic stress. Generally, on the basis of physiology, plant hormones roughly fall into two classes. In class one, phytohormones fall whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…This GO term includes genes involved in pathways of the aromatic amino acids, which are linked to the synthesis of several secondary metabolites such as phytohormones 44 . Phytohormones are known to regulate many processes such as flowering time and biomass production 41 , 45 . We found the molecular function voltage-gated chloride channel activity (417ChlCh) to be associated with chlorophyll content and stomata density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This GO term includes genes involved in pathways of the aromatic amino acids, which are linked to the synthesis of several secondary metabolites such as phytohormones 44 . Phytohormones are known to regulate many processes such as flowering time and biomass production 41 , 45 . We found the molecular function voltage-gated chloride channel activity (417ChlCh) to be associated with chlorophyll content and stomata density.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the relationship between gene expression and plant traits, we used redundancy analysis (RDA) performed in vegan package version 2.6-2 41 in R. The plant trait data (i.e. traits related to physiology, growth and fitness) were transformed as mentioned above and standardized for 0 mean and unit variance (to transfer all the traits into relative, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the effect was usually neutral or negative, which may be explained by the excessive concentration of phytohormones. In higher doses, phytohormones can inhibit important processes occurring in plants [37]. Additionally, recent studies on Lemna minor have shown that algal methanol extract can act similarly to herbicide [38].…”
Section: Discussionmentioning
confidence: 99%
“…The SA defense of plants is enhanced by cytokinin and thus cytokinin and salicylic acid exhibit a positive and beneficial interaction. A high level of cytokinin can modulate the SA signaling by triggering the SA-related gene expression involved in plant defense, thus, providing an enhanced protection to the plant (Lubyanova., 2021;Asif et al, 2022).…”
Section: Role Of Cytokinins In the Interaction Between Plants And Pat...mentioning
confidence: 99%